Introduction: language ideologies and the ‘Vernacular’: A critical perspective - Zaidi, Nishat; Harder, Hans (Language ideologies and the vernacular in colonial and postcolonial South Asia, 2023)
Languages rarely exist in an unmarked state of just being there. Communication about communication is probably as old as communication itself; likewise, reflection on language is not a new thing, especially if it comes to languages in the plural. Accordingly, among sociolinguists, language ideologies are understood as sets of assertions and beliefs about a language in a given milieu or society. Highly influential, and in some part responsible for the general trend of engaging again with the ‘vernacular’, is Sheldon Pollock’s model of vernacularization. The idea is that around the end of the first millennium AD, regional languages started moving into many domains of use, particularly literary ones, in which formerly Sanskrit had been dominant. Language ideologies in South Asia have played a pivotal role in the dynamics of power politics. In the process they unravel terrains of consciousness that are sites of continued contestations, claims and counter-claims and defy any easy logic of pure language or putative categorization.